Phytochemical Screening, Cytotoxicity and Antioxidant Activities of Leaves Extracts from Eucalyptus citriodora - Musa Maikudi Idris; Adamu Mohammed Yelwa; Aminu Muhammad (Journal of Tropical Pharmacy and Chemistry, 2021)
The genus Eucalyptus has been used in African traditional medicine for the treatment of cardiovascular diseases and diabetes. In this work, chloroform and methanol extracts from the leaves of Eucalyptus citriodora was investigated for their phytochemicals, cytotoxicity and antioxidant potentials. Phytochemical screening of the extracts showed the presence of alkaloid, flavonoid, phenols, reducing sugar and steroids in the methanol extract. IR absorptions of the extract supported the presence of these phytochemicals by revealing the bands 3335 cm-1 (O-H), 1613, 1480 cm-1 (C=C) and 1721 cm-1 (C=O). Evaluation of the cytotoxicity of the methanol extract using brine shrimp assay, suggested that, the extract was not toxic with LC50 value of 1.64 mg/mL. Antioxidant potentials of both chloroform and methanol extracts were determined using phenolic content quantification and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging. Methanol extract (37.32 ?g TAE/mg) had higher phenolic content than the chloroform extract (12.09 ?g TAE/mg). The radical scavenging potentials of the extracts recorded inhibitory activities of IC50 values of 892.7 ?g/mL (chloroform extract) and 8.3 ?g/mL (methanol extracts) relative to the positive control values of 31.1 ?g/mL (butylated hydroxytoluene) and 3.5 ?g/mL (ascorbic acid). These results showed that E. citriodora might contain promising antioxidant agents.